Early Social Enrichment Improves Social Motivation and Skills in a Monogenic Mouse Model of Autism, the Oprm1−/− Mouse - Luciana Garbugino; Eleonora Centofante; Francesca R. D’Amato (Neural Plasticity)
Environmental enrichment has been proven to have positive effects on both behavioral and physiological phenotypes in rodent models of mental and neurodevelopmental disorders. In this study, we used mice lacking the µ-opioid receptor gene (Oprm1−/−), which has been shown to have deficits in social competence and communication, to assess the hypothesis that early enrichment can ameliorate sociability during development and adulthood. Due to the immaturity of sensory-motor capabilities of young pups, we chose as environmental stimulation a second lactating female, who provided extra maternal care and stimulation from birth. The results show that double mothering normalized the abnormal response to maternal separation in Oprm1−/− pups and increased social motivation in juveniles and adult knockout mice. Additionally, we observed that Oprm1−/− mice act as less attractive social partners than wild types, which suggests that social motivation can be modulated by the stimulus employed. This experiment supports previous findings suggesting that early social environmental stimulation has profound and long-term beneficial effects, encouraging the use of nonpharmacological interventions for the treatment of social defects in neurodevelopmental diseases.